Software Language Engineering 6th International Conference, SLE 2013, Indianapolis, IN, USA, October 26-28, 2013. Proceedings - Erwig, Martin; Paige, Richard F.; Van Wyk, Eric (Programming and Software Engineering, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Software Language Engineering, SLE 2013, held in Indianapolis, IN, USA, in October 2013. The 17 technical papers presented together with 2 tool demonstration papers and one keynote were carefully reviewed and selected from 56 submissions. SLE's foremost mission is to encourage, synthesize and organize communication between communities that have traditionally looked at software languages from different and yet complementary perspectives. The papers are organized in topical sections on domain-specific languages; language patterns and evolution; grammars; tools; language analysis; and meta- and megamodelling.